The occurrence of asbestos-related diseases among former employees of asbestos processing plants in Poland - Beata Świątkowska (Nofer Institute of Occupational Medicine, 2019)
Background Despite the fact that asbestos is no longer used in production in Poland, there are still new cases of asbestos-related diseases among workers previously exposed to asbestos dust. This situation is related to the specificity of the biological activity of this mineral; the health consequences of asbestos can manifest not only during the exposure but also many years after exposure cessation. The aim of the analysis was to assess the occurrence of occupational diseases among people exposed to asbestos dust, who were examined under the Amiantus program. Material and Methods The research material consisted of the program cards filled by the doctors conducting the examinations as well as radiological images stored on the International Labour Organization form. The analysis covered 8049 people, including 37% of women surveyed in the years 2000−2017. Results In the group of former employees of asbestos processing plants, the occupational disease was diagnosed in 1993 people (25%), including 584 women (19%). The most common was asbestosis (76% of occupational diseases) and pleural disease (17%). Malignant neoplasms accounted for 7% of all cases in this group. The analysis showed an increase in the incidence of respiratory system diseases along with the age of the surveyed persons, their seniority at asbestos processing plants and an increase in cumulative exposure. The chest radiographs revealed radiological changes among 75% of the examined cases, whereas the changes entitling to diagnose asbestosis, according to the criteria applicable in Poland, occurred in 23% of the workers. The adoption of international criteria would increase the incidence of asbestosis as an occupational disease by 19% in the study group. Conclusions The increase in the percentage of people with a diagnosed occupational disease provides evidence for the worsening health status of the former workers as well as a good detection of asbestos-related diseases among employees exposed to asbestos dust in the past. The results of the analysis indicate the need for undertaking a discussion in Poland on the implementation of international criteria for the diagnosis of asbestosis. Med Pr. 2019;70(6):723-31